Hypoxia-inducible Factor: Basic Biology and Involvement in Cardiovascular Pathology - Soldatov, Vladislav O. (Asian Journal of Pharmaceutics (AJP), 2019)
The hypoxia-inducible factor (HIF) system plays a dominant role in the regulation of oxygen balance. There are three forms of HIF protein, whose function is being actively studied by the medical and biological environment. HIF-1 consists of Î±- and Î²-subunits. The Î±-subunit is destroyed under normoxia by oxygen-dependent enzymes such as prolyl hydroxylase domain and factor-inhibiting HIF-1. In hypoxic condition, a complex of HIF-1Î± and HIF-1Î² forms a transcription factor that controls the expression of several hundred genes. HIF-1 activity is primarily aimed at reducing mitochondrial respiration, activating glycolysis, and increasing the oxygen capacity of the blood and organs vascularization. Under hypoxic condition, HIF-1 reduces the activity of mitochondria, which prevents the generation of reactive oxygen species and protects the cells. On the transgenic animal models, as well as in the study of cardiac tissue biopsies in patients with myocardial infarction, the protective role of HIF in ischemic myocardial injuries was confirmed. During hypoxia of the brain, HIF plays an ambiguous role. There is evidence that astrocytic HIF-1 plays a negative role, and neuronal HIF-1 causes neuroprotection during hypoxia. The structure of HIF has a relatively low variability even in interspecific comparison. Molecular epidemiological studies conducted to date reveal a close relationship between the polymorphism of the HIF system genes with a wide range of cardiovascular, inflammatory, and oncological diseases. The study of the HIF system can contribute to the discovery of new targets and methods of pharmacological effects for the treatment of cardiovascular, oncological, rheumatological, and endocrinological pathology.